SYNTHESIS OF P- (2'-CARBOXYFERROCENYL) BENZOIC ACID (Scientific journal of the Fergana State University, 2023)
The article describes the synthesis of a new derivative of ferrocenecarboxylic acid with p-aminobenzoic acid, and also analyzes some of the physicochemical parameters of this substance and its field of application.